Characteristics and Treatment Outcomes of Propionibacterium acnes Prosthetic Shoulder Infections in Adults - Piggott, Damani A. (Open Forum Infect Dis, 2015)
Background. Prosthetic joint infections (PJIs) significantly complicate joint arthroplasties. Propionibacterium acnes is an increasingly recognized PJI pathogen, yet limited clinical and therapeutic data exist. We sought to examine characteristics of P. acnes shoulder PJIs and compare surgical and nonsurgical management outcomes. Methods. A retrospective analysis of P. acnes shoulder PJIs was conducted at an academic center in Baltimore, Maryland from 2000 to 2013. Results. Of 24 cases of P. acnes shoulder PJIs, 92% were diagnosed after extended culture implementation; 42% in the delayed and 46% in the late postsurgical period. Joint pain and diminished function were the predominant presenting clinical signs. Erythrocyte sedimentation rate and C-reactive protein elevations occurred in 47% and 44%, respectively. All tested isolates were susceptible to β-lactams, moxifloxacin, vancomycin, and rifampin. Clindamycin resistance was identified in 6%. Of the antibiotic-only treated cases, 67% had a favorable clinical outcome compared with 71% (P = 1.0) of cases with a combined antibiotic-surgical approach. Favorable outcome with and without rifampin therapy was 73% and 60% (P = .61), respectively. Conclusions. Propionibacterium acnes PJI diagnoses increased with extended culture. Inflammatory markers were elevated in a minority of cases. Isolates maintained broad antimicrobial susceptibility. Compared to combined antibiotic-surgical approaches, antibiotic-only approaches were similarly successful in selected cases.